The periodontal health component of the Renal Impairment In Secondary Care (RIISC) cohort study: a description of the rationale, methodology and initial baseline results. (14th May 2014) - Sharma, Praveen; Dietrich, Thomas; Sidhu, Amneet; Vithlani, Viren; Rahman, Mutahir; Stringer, Stephanie; Jesky, Mark; Kaur, Okdeep; Ferro, Charles; Cockwell, Paul; Chapple, Iain L. C.
Abstract Introduction Chronic kidney disease (CKD) is associated with significant morbidity and mortality. There is a need to identify novel and modifiable risk factors in such patients. The periodontal component of the Renal Impairment In Secondary Care (RIISC) study aims to evaluate the association between chronic periodontitis and CKD progression. Methods The RIISC study is a prospective, observational cohort study of patients with CKD from a renal clinic at a hospital in the West Midlands region of the UK. Patients undergo a periodontal examination and plaque and saliva sampling. To benchmark the oral health status of the RIISC cohort, we compared it to the Adult Dental Health Survey 2009 (ADHS), a representative survey of the oral health of community dwelling adults in the UK. Results Of the first 500 patients recruited into the RIISC study, 469 patients underwent a dental examination and 80 (17%) were edentulous. Among dentate subjects, patients within RIISC were significantly more likely to have any (OR 4.0 95% CI 2.7–5.9) or severe (OR 3.8 95% CI 2.5–5.6) periodontitis compared to the ADHS sample. Conclusion The prevalence and severity of chronic periodontitis in this cohort of CKD patients is markedly higher than a geographically matched control population.